Urgency Arrangement Mediation in Dispute Tax as Instrument Non- Litigation Alternatives - Sara, Rineke; Defry Yusdanial, Raden Ferdiandra (International Journal Labs, 2025)
Dispute tax is a common problem faced by the state and mandatory tax, which can bother state revenue and cause uncertainty in law. Settlement process dispute taxes in Indonesia are generally done through track litigation in court Taxes, which often take up a long time, cost high, and cause tension between parties involved. As response to challenge said, article This to study urgency arrangement mediation as alternative settlement dispute taxes. Mediation, which is a dispute resolution process dispute outside court involving a neutral mediator, it is hoped can give more solutions efficiently, reduce burden court, and facilitate more solutions fair for the second split party. Through approach juridical-normative and studies comparative towards countries that have applied mediation in dispute taxes, such as the Netherlands, Australia, and the United States, article This highlights benefit mediation in context taxation. Arrangement mediation in dispute tax considered important for increase efficiency administration tax, reduce cost litigation, as well as create more relationship constructive between authority tax and obligation tax. Article this also suggests changes and improvements necessary regulations to support implementation mediation in settlement dispute taxes in Indonesia, to realize a system more taxation transparent and accountable.